Democracy administered : how public administration shapes representative government - Bertelli, Anthony Michael (Cambridge : Cambridge University Press, 2021)
How does representative government function when public administration can reshape democracy? The traditional narrative of public administration balances the accountability of managers, a problem of control, with the need for effective administration, a problem of capability. The discretion modern governments give to administrators allows them to make tradeoffs among democratic values. This book challenges the traditional view with its argument that the democratic values of administration should complement the democratic values of the representative government within which they operate. Control, capability and value reinforcement can render public administration into democracy administered. This book offers a novel framework for empirically and normatively understanding how democratic values have, and should be, reinforced by public administration. Bertelli's theoretical framework provides a guide for managers and reformers alike to chart a path toward democracy administered.
Title from publisher's bibliographic system (viewed on 20 Aug 2021).
Keywords: Public administration -- Evaluation; Democracy; Representative government and representation; Government accountability; Administrative agencies -- Management